(untitled) (Journal of actual problems of jurisprudence, 2018)
The article examines the legal nature of the principle of freedom to appeal procedural actions and decisions as the fundamental and guiding principle of the whole criminal process of the Republic of Kazakhstan. The subject of the study are: the system of legislative and other normative legal acts of the current legislation of the Republic of Kazakhstan; regulated by them a circle of homogeneous social relations on the implementation of the principle of freedom to appeal procedural actions and decisions in criminal proceedings; the practice of applying the above legislation, on the basis of which study proposals are being developed to improve legislation, as well as studies of law enforcement practice on the issues under consideration in the Republic of Kazakhstan. The methodological basis of the scientific article was the political, legal, philosophical, legal and other scientific justifications for the principles and procedures for carrying out the constitutional basis for the legal regulation of the citizens’ right to personal freedom, as well as for the principle of freedom of appeal of procedural actions and decisions in the criminal process. For this, general scientific and private scientific methods of studying state and legal phenomena were applied. The scientific novelty lies in the fact that the author, using the imperial scientific material, justifies the approaches of adequate provision in the criminal procedural code of the Republic of Kazakhstan to the protection of citizens who fall into the sphere of the criminal process from encroachments on their legitimate rights and freedoms on the part of criminal prosecution authorities. The need for further improvement of the legislation defining the legal regime of the institution of appeal with the aim of creating a system of procedural guarantees for the rights, freedoms and legitimate interests of the individual in criminal proceedings is being updated. The issues on the need to provide detainees with the right to appeal the legality and validity of the detention are considered. Key words: the principle of freedom of appeal of procedural actions and decisions, criminal process, court, prosecutor’s office, detention, detention.